Approaches to the Detection of Internal Control and Audit - Rusudan Kutateladze; Anzor Abralava; Nino Pailodze; Nino Taruashvili; Iasha Murvanidze (Journal of Management Practices, Humanities and Social Sciences, 2020)
The purpose of this research is to define approaches and control measures to the internal control and audit system in the economic entity, which is a key function of internal audit. The urgency of the research topic is driven by the need to improve the control system, which is one of the important factors for countries in transition economies. The methodological basis of the research was provided by the papers of Georgian and foreign scientists dedicated to the internal control of the corporation and specifically to the internal audit. The methodological basis of the research has become the dialectical method of studying economic events and processes. In addition, general and specific scientific methods of knowledge of events and facts were used. This study developed a set of documentation for performing control procedures that will reduce the time required for calculations and increase object verification accuracy. This study provides insights for scholars and practioners and encourages them to systematically analyze the audit and its development directions.